Prosedur Tindakan Percutaneous Coronary Interventional dengan kasus Chronik Total Occlusion Pada Arteri Koroner - Astuti Juniarti Daing; Kusman Kusman (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Percutaneous coronary interventional (PCI) is a minimally invasive blood vessel widening procedure using balloons and stents, the PCI procedure in CTO cases uses the double puncture technique and the C-arm tube angle position LAO 45 ? - Cranial 15 ? and Frontal 0 ? - Cranial 30 ?. The aim of using the double puncture technique is to see the entry point and exit point of chronic total occlusion. This study aims to find out the latest literature related to PCI procedures in CTO cases, including current developments and status. This research is a literature review (Summary Method) where literature exploration is carried out using various sources with the keyword